The Specification of Institutional Features in the Determination of Wages in Canadian Manufacturing Industries - J.C.R. Rowley; D.A. Wilton (Queen's University, Department of Economics, 1972)
As demonstrated in a recent paper, quarterly models of wage determination are highly sensitive, both with respect to parametric estimates and statistical inferences, to the specification of institutional features in the labour market. In the context of these sensitivities, this paper attempts to eliminate a severe deficiency in relevant data by the provision, in tabular form, of time-series which summarize evidence for critical institutional features of the Canadian labour market. The first section contains a brief overview of the data set and examines certain issues such as the coverage of the sample, seasonal patterns in bargaining, and the average lengths of contracts. This overview is followed in the second section by an account of a particular analytical model which incorporates these institutional features in a form appropriate for estimation of behavioural parameters. Finally, some statistics for the institutional characteristics of the labour market (by reference to the analytical model) are provided in the form of a collection of variable weights. These weights will be employed in a subsequent paper for which the behavioural parameters of the market will be estimated.
Keywords: 330